Learning in Public Policy Analysis, Modes and Outcomes (Cham : Springer International Publishing, 2018)
This book explains the causal pathways, the mechanisms and the politics that define the quantity and quality of policy learning. A rich collection of case studies structured around a strong conceptual architecture, the volume comprises fresh, original, empirical evidence for a large number of countries, sectors and multi-level governance settings including the European Commission, the European Union, and individual countries across Europe, Australia, Canada and Brazil. The theoretically diverse chapters address both the presence of learning and its pathologies, deploying state-of-the-art methods, including process tracing, diffusion models, and fuzzy-set techniques. Claire A. Dunlop is Professor of Politics at the Department of Politics at the University of Exeter, UK. She is editor of Public Policy and Administration. Claudio M. Radaelli is Professor of Political Science, Jean Monnet Chair in Political Economy and Director of the Centre for European Governance at the University of Exeter, UK. Philipp Trein is a senior researcher in political science at the IEPHI (Institute of Political, Historical, and International Studies) of the University of Lausanne, Switzerland.
1 Introduction: The Family Tree of Policy Learning. Claire A. Dunlop, Claudio M. Radaelli and Philipp Trein -- 2 Lessons Learned and Not Learned: Bibliometric Analysis of Policy Learning. Nihit Goyal and Michael Howlett -- 3 Learning in the European Commission's Climate and Renewable Energy Policy-Making. Katharina Rietig -- 4 Mechanisms of Policy Learning in the European Semester: Pension Reforms in Belgium. Christos Louvaris Fasois -- 5 Individual Learning Behaviour in Collaborative Networks. Vidar Stevens -- 6 Learning from Practical Experience: Implementation Epistemic Communities in the European Union. Daniel Polman -- 7 The Rise and Demise of Epistemic Policy Learning: The Case of EU Biotechnology Regulation. Falk Daviter -- 8 Public versus Non-Profit Housing in Canadian Provinces: Learning, History and Cost-Benefit Analysis. Maroine Bendaoud -- 9 Blocked Learning in Greece: The Case of Soft-Governance. Thenia Vagionaki -- 10 Structure, Agency and Policy Learning: Australia's Multinational Corporations' Dilemma. Tim Legrand -- 11 Median Problem Pressure and Policy Learning: An Exploratory Analysis of European Countries. Philipp Trein -- 12 The Hard Case for Learning: Explaining the Diversity of Swiss Tobacco Advertisement Bans. Johanna Künzler -- 13 The Policy-Making of Investment Treaties in Brazil: Policy Learning in the Context of Late Adoption. Henrique Choer Moraes and Martino Maggetti -- 14 Interdependent Policy Learning: Contextual Diffusion of Active Labour Market Policies. Jan Helmdag and Kati Kuitto.
Political Science and International Studies
text file PDF
Keywords: Public policy; Political theory; Legislative bodies; Social policy; Public administration; European Union